2013
DOI: 10.1371/journal.pone.0060686
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Study of Supraspinal Input and Spinal Output of Cat's Subnucleus Reticularis Dorsalis (SRD) Neurons

Abstract: This work addressed the study of subnucleus reticularis dorsalis (SRD) neurons in relation to their supraspinal input and the spinal terminating sites of their descending axons. SRD extracellular unitary recordings from anesthetized cats aimed to specifically test, 1) the rostrocaudal segmental level reached by axons of spinally projecting (SPr) neurons collateralizing or not to or through the ipsilateral nucleus reticularis gigantocellularis (NRGc), 2) whether SPr fibers bifurcate to the thalamus, and 3) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…One possible target is to enhance the endogenous pain modulation system before pain arises. The endogenous pain modulation system in healthy population and acute pain conditions have the ability to deal with nociceptor stimuli via supraspinal structures as primary motor and sensory cortices, the thalamus, the cingulate cortex, the periaqueductal gray, the rostral ventromedial medulla and the connection with the subnucleus reticularis dorsalis and projections to the spinal cord [177][178][179][180][181]. However, this pathway is impaired in chronic pain leading to an unbalance on the endogenous pain pathway.…”
Section: Tdcs To Prevent Painmentioning
confidence: 99%
“…One possible target is to enhance the endogenous pain modulation system before pain arises. The endogenous pain modulation system in healthy population and acute pain conditions have the ability to deal with nociceptor stimuli via supraspinal structures as primary motor and sensory cortices, the thalamus, the cingulate cortex, the periaqueductal gray, the rostral ventromedial medulla and the connection with the subnucleus reticularis dorsalis and projections to the spinal cord [177][178][179][180][181]. However, this pathway is impaired in chronic pain leading to an unbalance on the endogenous pain pathway.…”
Section: Tdcs To Prevent Painmentioning
confidence: 99%
“…The DRt is also a major integrative relay for descending nociceptive modulation from several brain areas including the cortex (Zhang et al, 2005 ), the hypothalamus (Amorim et al, 2015 ) and the brainstem (Martins et al, 2013 ; Velo et al, 2013 ; Leiras et al, 2016 ). The DRt was shown to relay descending pain facilitation from the anterior cingulate cortex (ACC; Zhang et al, 2005 ).…”
Section: The Rvm-vlm-drt Triad As a Key Gateway For Top-down Pain Modmentioning
confidence: 99%
“…These regions include the periaqueductal gray (PAG) in the midbrain; the parabrachial complex (PB) and locus coeruleus (LC) in the pons; and the rostral ventromedial medulla (RVM) and subnucleus reticularis dorsalis (SRD) in the medulla. Neuroanatomical tract tracing revealed that each of these brainstem regions projects directly to, or receives projections from, both the DH and SpV [4][5][6][7][8]. Modern brain imaging has revealed that these pathways are likely conserved in humans, and with the advent of ultra-high field magnetic resonance imaging (MRI), we have begun to better define their contributions to pain modulation in both experimental and clinical settings, as well start to robustly characterize the manner in which these brainstem sites interact with one another [9 && ].…”
Section: Brainstem Circuitry Involved In Pain Transmission and Modula...mentioning
confidence: 99%